2013
DOI: 10.1074/jbc.m112.419317
|View full text |Cite
|
Sign up to set email alerts
|

PRIP (Phospholipase C-related but Catalytically Inactive Protein) Inhibits Exocytosis by Direct Interactions with Syntaxin 1 and SNAP-25 through Its C2 Domain

Abstract: Background: PRIP inhibits exocytosis, but the underlying mechanism is unknown. Results: PRIP interacts with syntaxin-1 and SNAP-25 through its C2 domain and inhibits SNARE complex formation. Conclusion: Inhibition of exocytosis by PRIP is attributed to the direct binding to SNAREs and the inhibition of SNARE complex formation. Significance: PRIP is a new member of SNARE-binding proteins bearing C2 domain that are involved in regulating exocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…gesting that the higher secretion of gonadotropin that was observed does not occur through a feedback loop in the HPG axis (25). These results and our previous studies suggest that PRIPs are negatively involved in exocytosis in the pituitary gland, which leads to the secretion of peptide hormones (12,13,25).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…gesting that the higher secretion of gonadotropin that was observed does not occur through a feedback loop in the HPG axis (25). These results and our previous studies suggest that PRIPs are negatively involved in exocytosis in the pituitary gland, which leads to the secretion of peptide hormones (12,13,25).…”
supporting
confidence: 73%
“…They were named because they lacked catalytic activity, despite having a domain organization that is similar to phospholipase C-␦1, which includes a pleckstrin homology (PH) domain, EF-hand motifs, catalytic X and Y, and C2 domains (6, 7). Several interacting partners have been identified for PRIPs, including ␥-aminobutyric acid type A (GABA A ) receptor-associated protein (8), the ␤ subunit of the GABA A receptor (9), the catalytic subunits of protein phosphatase 1␣ and 2A (9, 10), the phosphorylated form of Akt (11), and SNARE proteins (12,13), in addition to Ins(1,4,5)P 3 and phosphatidylinositol 4,5-bisphosphate (14,15). The discovery of these binding partners led to the identification of the involvement of PRIPs in Ins(1,4,5)P 3 / Ca 2ϩ signaling (14,16), GABA A receptor signaling (17-19), protein dephosphorylation (20, 21), and exocytosis (12, 13).…”
mentioning
confidence: 99%
“…Phospholipase C Like 1, inactive (PLCL1) was up-regulated in response to RIF exposure ( Fig 5D). PLCL1 is involved in the inhibition of exocytosis through its interactions with syntaxin 1 and SNAP-25 [40].…”
Section: Enriched Canonical Pathways Following Exposure To Pbdes Citmentioning
confidence: 99%
“…Later, an isoform with relatively broad tissue distribution, including the brain, was reported, comprising PRIP‐1 and ‐2 [Kikuno et al, ; Otsuki et al, ; Uji et al, ]. Subsequent studies revealed that there are a number of binding partners, including GABARAP [γ‐aminobutyric acid type A (GABA A ) receptor‐associated protein] [Kanematsu et al, ], the catalytic subunit of protein phosphatase 1 and 2A [Yoshimura et al, ; Terunuma et al, ; Kanematsu et al, ; Yanagihori et al, ; Gao et al, ], the phosphorylated (active) form of Akt [Fujii et al, ], the β subunits of the GABA A receptor [Terunuma et al, ; Kanematsu et al, ; Kanematsu et al, ] and SNARE proteins, syntaxin 1 and SNAP‐25 [Gao et al, ; Zhang et al, ], in addition to inositol 1,4,5‐trisphosphate.…”
mentioning
confidence: 99%
“…We further generated PRIP gene‐deficient mice, in each subtype or both and performed analyses of the phenotypes for information regarding the physiological functions mainly using PRIP‐1 and ‐2 double knock out (KO) mice, since binding properties to some of the above‐mentioned molecules provided little difference between PRIP‐1 and ‐2. Binding partners with known functions helped the analyses: inositol 1,4,5‐trisphosphate‐mediated Ca 2+ signaling [Takeuchi et al, ; Harada et al, ], GABA A receptor signaling [Kanematsu et al, , , ; Terunuma et al, ; Mizokami et al, , ; Fujii et al, ], phospho‐regulation through phosphatase swapping [Sugiyama et al, ] and negative regulation of exocytosis [Gao et al, ; Zhang et al, ].…”
mentioning
confidence: 99%